Knowledge on Endotracheal Tube Care Among Nurses in A Hospital - Mandal, Reena; Rai, Mamta; Mahato, Ranju (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Endotracheal Tube (ETT) care management, play a significant role in the course of recovery of critically ill patients with ET tube. Oral and endotracheal suctioning of secretions, monitoring ETT cuff pressure, and the provision of oral care are all part of daily care. This study was carried out with the aim of assessing knowledge on endotracheal tube care among nurses in Manmohan Memorial Medical College and Teaching Hospital, Swoyambhu, Kathmandu Method: A descriptive cross-sectional study was conducted among 110 nurses of MMTH using stratified proportionate sampling technique. Self-administered questionnaire technique was used to collect data by using Self-developed structured questionnaire. Data analysis was done using descriptive and inferential statistics in SPSS version 23 Results: The result showed that inadequate knowledge was present in frequency of endotracheal suctioning (20.0%), appropriate depth of suction catheter insertion (29.1%), suction pressure method (24.5%), appropriate duration for endotracheal suctioning (23.6%), complication of over-inflation (26.4%) and oral cavity assessment (13.6%). The findings of the study showed that half (50.0%) of the nurses had adequate level of knowledge on ETT care. The study shows the significant association of the level of knowledge on ETT care with ethnicity (p=0.022) and working unit (p=0.021). Conclusion: There is still gap in knowledge on ETT care. To improve the nurse’s knowledge on ETT care, education and communication activities should be increased through in-service education and training focusing on endotracheal tube suctioning, cuff pressure monitoring and oral care of intubated patients